Implementation of Information Technology in Human Resource Management - Soegeng Wahyoedi; Suherlan Suherlan; Syamsu Rijal; Hizbul Khootimah Azzaakiyyah; Abu Muna Almaududi Ausat (Al-Buhuts, 2023)
This research aims to discuss the implementation of information technology in HR management by adopting the theory of Technology Acceptance Model and Diffusion of Innovation. This research is qualitative in nature by reviewing relevant literature. Data collection techniques included listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The results of this study show that the use of information technology can provide various benefits for HR management, such as increasing efficiency, accelerating the decision-making process, and reducing operational costs. The results of this study are also expected to provide added value in decision making for companies in managing their HR.